Health interventions and risky behaviour - David Madden (University College Dublin, UCD School of Economics, 2007)
This paper reviews the extent to which policy interventions can affect risky behaviours such as smoking, drinking and diet. The justification for such intervention is typically a market failure, broadly defined. The types of market failure typically encountered are discussed. First and second best interventions are examined and there is a review of the efficacy of such interventions with respect to Ireland.
Keywords: I12; I18; D62; 330; risky behaviour; market failure; Gesundheitsrisiko; Rauchen; Alkoholkonsum; Marktversagen; Gesundheitspolitik; Wohlfahrtseffekt; Irland